The Panathenaic amphorae: an instrument for the propagation of Athens’ discourse and a subject of symbolic conflict (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
Visual arts represent one way of transmitting different ideas and messages, from personal preferences of subjects to political identities. The Antiquity is not an exception from this practice. An excellent example of illustrating a political discourse, through a type of visual art, is found in the iconography of the Panathenaic amphorae, the prize vases from the Great Panathenaea.The focus of this paper is the Panathenaics from the Great Panathenaea of 402 BC, represented by four pieces discovered in Libya. These four vases stand out by having the statuary group of the Tyrannicides decorating Athena’s shield on the obverse side. This element of iconography will be analysed from the perspective of the symbolic conflict theory of Simon Harrison.
Keywords: Panathenaic amphorae; tyrannicides; symbolic conflict; circulation of ceramics; Athens